Aging delay: of mice and men - Anisimov, Vladimir (Acta Biomedica Atenei Parmensis, 2021)
The evaluation of the safety of a drug in rodents that may be used as geroprotectors is a challenge of current times. In the paper, we discuss approaches to long-term assays for selection of potent aging delay drugs for humans. Priority is given to methods combining evaluation of carcinogenic safety and life-spanning potential. The use of such methods will be time-efficient and economically feasible.